2022
DOI: 10.3390/v14071426
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early Antiretroviral Treatment (ART) for HIV on the Sensitivity of the Latest Generation of Blood Screening and Point of Care Assays

Abstract: Introduction: Rapid initiation of antiretroviral therapy (ART) in early HIV infection is important to limit seeding of the viral reservoir. A number of studies have shown that if ART is commenced prior to seroconversion, the seroconversion may, or may not, occur. We aimed to assess whether seroreversion or no seroconversion occurs using samples collected during an early treatment study in South Africa. Methods: We tested 10 longitudinal samples collected over three years from 70 blood donors who initiated ART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…High CD4 + counts and high viral load suppression make ART more likely to be successful [ 5 ], and the initiation of antiviral therapy in patients with CD4 + counts above 500 cells/μl significantly reduces the combined endpoint events of mortality and morbidity [ 5 , 6 ] and reduces the risk of drug resistance [ 7 ], reduced CD4 + counts, impaired cellular immune function, and immunity. The more severe the deficiency, the longer the required immune reconstitution takes and the higher the failure rate of ART, based on which it is recommended that ART be initiated rapidly in patients with HIV/AIDS [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…High CD4 + counts and high viral load suppression make ART more likely to be successful [ 5 ], and the initiation of antiviral therapy in patients with CD4 + counts above 500 cells/μl significantly reduces the combined endpoint events of mortality and morbidity [ 5 , 6 ] and reduces the risk of drug resistance [ 7 ], reduced CD4 + counts, impaired cellular immune function, and immunity. The more severe the deficiency, the longer the required immune reconstitution takes and the higher the failure rate of ART, based on which it is recommended that ART be initiated rapidly in patients with HIV/AIDS [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of HIV infection among the prospective blood donors using the WHO-recommended two-test diagnostic technique (the conventional rapid test and the p24 antigen ELISA) raised confidence in the specificity of the blood before transfusion. Misdiagnosis of HIV can cause mental illness and public health repercussions and should thus be avoided to the extent possible [9,10,24]. Knowledge, practices, and risk studies are valuable tools deployed to assess the extent to which individuals adopt risk-free behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…HIV/AIDS control depends on an accurate laboratory HIV infection diagnosis [9,10]. Rapid HIV-1/2 antibody-based point-of-care (POC) tests are evolving and making HIV testing feasible in the developing world [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If collected and transfused, such blood can transmit small amounts of potentially infectious virions to the recipient. Vermeulen and colleagues [ 9 ] addressed this concern in regard to South African blood donors and concluded that donors on ART may constitute a HIV transmission risk when relying on less sensitive serological rapid tests for screening, as is frequently the case in resource-limited countries. Although the risk appears to be extremely low when using the latest generation of high-throughput serological tests, further studies are required to monitor this emerging risk to blood safety.…”
mentioning
confidence: 99%